“Desarrollo de un aplicativo móvil offline para las rutas turísticas de Malqui Machay” - Lopez Velez, Bryan Alejandro (2023)
The project objective is to develop an offline mobile application oriented to Android devices for the tourist routes of Malqui Machay, which allows the user to know the different access routes to reach the ceremonial center. This application is developed by working on the Mobile-D Methodology, which resulted in excellent performance and facilitated the selection of the tools used, which are the Android Studio IDE for carrying out the development of the program, XML for the design of the application, the Java programming language, a database of SQLite embedded data for entering route and establishment data, and Mapbox, as this is an open source library that allows Android application developers to create custom maps, among others that will help to develop the application. As a result, it obtained a user-friendly offline navigation mobile application, which will only use the internet at the time of download and for its respective updates, and has a web system where you can modify, update, enter, and delete the information within the application. Finally, as for functionality terms, the application favors its use in the areas surrounding Malqui Machay since they are sectors that do not have an internet connection.